Answer:
67
Step-by-step explanation:
subtract 90 from 23 and you should have what you need to save.
9514 1404 393
Answer:
(x, y) = (-5, -6)
Step-by-step explanation:
The coefficients of y are the same, so we can eliminate y by subtracting one equation from the other. Here, we choose to subtract the first from the second, so that the coefficient of x ends up positive.
(-5x +5y) -(-6x +5y) = (-5) -(0)
x = -5 . . . . . . simplify
-6(-5) +5y = 0 . . . . . . substitute x into the first equation
6 +y = 0 . . . . . . . . . . divide by 5
y = -6 . . . . . . subtract 6
The solution to the system of equations is (x, y) = (-5, -6).
Answer:
49 dollars
Step-by-step explanation:
700 times .07
6((3 * 10) + (4 * 12)).....ur expression
6(30 + 48)
6(78)
468 cookies in 6 days